Production and characterization of a monoclonal antibody against recombinant saposin-like protein 2 of Fasciola gigantica - Pornanan Kueakhai (2018)
A monoclonal antibody (MoAb) against recombinant Fasciola gigantica saposin-like protein 2 (rFgSAP-2) was produced by hybridoma technique using spleen cells from BALB/c mice immunized with rFgSAP-2. This MoAb is an IgG1, κ light chain isotype. By immunoblotting and indirect ELISA, the MoAb reacted specifically with rFgSAP-2, the natural FgSAP-2 at 10. kDa in whole body (WB) and excretory-secretory (ES) fractions of F. gigantica. It did not cross react with antigens in WB fractions from other parasites, including Opisthorchis viverrini, Schistosoma mansoni which are human parasites, Haemonchus placei, Setaria labiato-papillosa, Eurytrema pancreaticum, Cotylophoron cotylophorum, Fischoederius cobboldi, Gigantocotyle explanatum, Gastrothylax crumenifer, and Paramphistomum cervi which are ruminant parasites. By immunohistochemistry, the FgSAP-2 protein was localized only in the cytoplasm of caecal epithelial cells of 4-week-old juvenile and adult stages, but not in metacercariae, newly excysted juvenile (NEJ), 2- and 3-week-old juveniles. This finding indicated that FgSAP-2 is an abundantly expressed parasite protein that is released into the ES, hence SAP-2 and its MoAb may be used for immunodiagnosis of ruminant and human fasciolosis. © 2012 Elsevier B.V.